Utilizing the Inshot Application as A Distance Learning Video - Septika Rudiamon; Delti Kurnia; Ramesh Prasad Adhikary (Journal International Inspire Education Technology, 2022)
Distance learning at this time results in low delivery of learning materials and learning objectives are not achieved optimally, because teachers only give assignments without learning video learning media, so students do not really understand the learning material, teachers must make learning media at the same time. distance learning by utilizing advanced technology such as using inshot editing applications in learning videos. The goal is for teachers to better know, understand, and increase knowledge about the use of the inshot video editing application as a learning video editing application during the pandemic, because by knowing how to activate learning videos in the inshot application, teachers or it will be easy to make easy, interesting learning videos. , simple, simple. This inshot application has enough features, various features that can be tried for free without paying, this application can be downloaded via the Google Play store on smartphones. And there are several existing features of the inshot application that can be used such as video, split video in two parts or on several clips, adjust video speed, can speed up or slow down video editing, feature to add live audio recording, can control video volume, can rotate videos, Export video files with HD quality, and can crop or remove watermarks on videos. the advantage of the inshot application in video is that it is easy to find information, many interesting features, and can also set the size of the canvas or video size, can share to social media, the inshot application is very suitable for beginners or make simple videos without being complicated and will not interfere when uploading videos.